(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
The paper is about the largest landfill in Latvia Getlini. Waste from Riga city and surroundings are disposed here. The waste landfilling once was started in the old sand-gravel quarry, next to the Getlini bog, and no environment protection measures were taken. Currently total area of the Getlini landfill is 87 ha and 36 ha of it occupy the old dumpsite (waste hill). Contaminants from the waste with storm water leached to the over groundwater and under groundwater and contaminated it. In the paper contamination level and spreading of leachate, surface water and groundwater are described.